Introduction of a fungal NADP(H)-dependent glutamate dehydrogenase (gdhA) improves growth, grain weight and salt resistance by enhancing the nitrogen uptake efficiency in forage rice. (2nd April 2016) - Zhang, Haibo; Liang, Chenggang; Aoki, Naohiro; Kawai, Kiyoshi; Takane, Ken-ichi; Ohsugi, Ryu
Abstract: We report the effect of the introduction of a fungal glutamate dehydrogenase gene ( gdhA ) into forage rice (cv. Momiroman) by analyzing the transgenic rice plants in terms of growth, source function, and nitrogen contents. NADP (H)-dependent glutamate dehydrogenase activities in the gdhA -transgenic lines were markedly higher than those in non-transgenic control plants. Plant growth analysis at the seedling stage revealed that the leaf area and shoot and root dry weights of the high gdhA -expressors were higher than those of control plants under both high (high N) and low nitrogen (low N) conditions. These results suggested that the source ability was enhanced by the gdhA introduction. This was supported by the fact that the net photosynthesis rate at the heading stage was also higher in transgenic than in control leaves. Furthermore, under both high and low N conditions, the nitrogen contents in the shoots and roots, at seedling and grain-harvest stages, were significantly higher in high gdhA -expressors than in control plants, indicating that nitrogen uptake was higher in transgenic than in control plants. At the harvest stage, the high gdhA -expressors exhibited greater panicle and spikelet numbers per plant compared with control plants, resulting in higher grain weight, under the high N conditions. In addition, gdhA expression in forage rice significantly enhanced their tolerance to salt stress compared to control plants. The present study showed that the introduction of a fungal gdhA into forage rice could lead to higher source ability, better growth and higher grain weight by enhancing nitrogen uptake efficiency.